Les jeunes adultes québécois et le crédit - Marie J. Lachance; Pierre Beaudoin; Jean Robitaille (Enfances, Familles, Générations, 2005)
This paper deals with an evaluation of the attitudes and practices of Quebecers aged between 18 and 29 with regard to credit and the nature and level of their debt burden. Survey results indicate that their use of credit instruments is fairly high, but their knowledge of how they function is slender. They have diverse attitudes to credit and indebtedness, and a majority of them lay claim to socially positive practices. Over 75 % of those surveyed have at least one debt, most usually their student loan, followed by the unpaid balance of a credit card. This study confirms that the use of credit and the number of young people with debts have increased considerably over the past ten years.